Rates of hospitalization for urinary tract infections among medicaid-insured individuals by spina bifida status, Tennessee 2005–2013. Issue 4 (October 2020) - Gebretsadik, Tebeb; Cooper, William O.; Ouyang, Lijing; Thibadeau, Judy; Markus, Tiffanie; Cook, Jessica; Tesfaye, Sarah; Mitchel, Edward F.; Newsome, Kimberly; Carroll, Kecia N.
Abstract: Background: Individuals with spina bifida are at increased risk for urinary tract infection (UTI), however there are few population-based investigations of the burden of UTI hospitalizations. Objective: We assessed rates and risk factors for UTI hospitalization in individuals with and without spina bifida. Methods: We conducted a retrospective cohort study to estimate rates of UTI hospitalization by spina bifida status. We included individuals enrolled in Tennessee Medicaid who lived in one of the Emerging Infections Program's Active Bacterial Surveillance counties between 2005 and 2013. Spina bifida was primarily defined and UTI hospitalizations were identified using International Classification of Diseases, Ninth Revision diagnoses. We also studied a subset without specific health conditions potentially associated with UTI. We used Poisson regression to calculate rate ratios (RR) of UTIs for individuals with versus without spina bifida, adjusting for race, sex and age group. Results: Over the 9-years, 1, 239, 362 individuals were included and 2, 493 met criteria for spina bifida. Individuals with spina bifida had over a four-fold increased rate of UTI hospitalization than those without spina bifida-in the overall study population and in the subset without specific, high-risk conditions (adjusted rate ratios: 4.41, 95% confidence intervals: 3.03, 6.43) and (4.87, 95% CI: 2.99, 7.92), respectively. We detected differences in rates of UTI hospitalization by race and sex in individuals without spina bifida that were not seen among individuals with spina bifida. Conclusions: Individuals with spina bifida had increased rates of UTI hospitalizations, and associated demographic patterns differed from those without spina bifida.